A study of the association of leukopenia with disease severity and mortality in patients diagnosed with COVID-19 - Parasher, Anant; Saini, Vishakha; Saini, Ajay; Barik, Rashmi Ranjan; Aggarwal, Abhinav; Khan, Javed (International Journal of Advances in Medicine, 2020)
Background: It has been observed in patients suspected with COVID-19 or presenting as confirmed cases of COVID-19 that a decreased total white blood cell count (leukopenia) is quite a common haematological presentation. In this study we aimed to determine the effect of leukopenia on the progress and severity of COVID-19, as well as to establish the association of leukopenia with disease severity and overall mortality. Methods: This was a longitudinal study conducted at Guru Teg Bahadur hospital, New Delhi from 1st July 2020 to 3rd August 2020. A sample size of 34 cases each in two groups (group A and B) was taken as one random case each day for the duration of the study; group A consisting of the patients presenting with leukopenia, while group B comprising of the patients with a normal leukocyte count. Results: The mean duration of hospital stay in group A was found to be 5.5±2.23 days, while the mean duration of stay in group B was found to be 2.9±1.17 days, showing a significant difference in the two groups with a p<0.001. It was also seen that a total of 8 out of 34 cases in group A and 2 out of the 34 cases in group B had expired during their hospital stay; a significant difference seen among the two groups with a p=0.04. Conclusions: Thus, in conclusion, this study demonstrates a definite and significant association between a decreased leukocyte count (leukopenia) and disease severity and mortality in patients with COVID-19.